ALKHAIRAAT POLITICAL KHARISMA - Syamsuri, Syamsuri (Hunafa: Jurnal Studia Islamika, 2019)
Abstract.Alkhairaat, founded in 1930, is the largest social organization (CSO) in Central Sulawesi Province, which has regional and branch managers in various provinces in Eastern Indonesia. Charitable business is engaged in education, preaching, social, cultural, media, economic and health. The educational institutions managed by this mass organization number 1,596, starting from the level of Early Childhood Education to Higher Education. Existing in Dutch and Japanese colonial times, Alkhairaat has a heroic history that gave birth to organizational charisma. The foundation of organizational ideology comes from the charism of Sayyid Idrus bin Salim Aldjufri as the founder of Alkhairaat. The scientific heritage of the Muslim community has led to massive sympathy for Alkhairaat. Alkhairaat's massification has become a political momentum since the opening of Indonesia's democratic reform taps in 1998. Several political parties have come to the Alkhairaat organization to recruit political cadres in the face of general election events.Alkahiraat's political charisma in the frame of political communication includes the participation, consolidation, and partnership of Alkhairaat politicians who spread in various political parties to win the election contestation. Election of members of parliament, regional heads, to the President and Vice President of the Republic of Indonesia. Alkhairaat’s charisma becomes an image commodity (popularity) to get elective support in every political contestation. Keywords: participation, popularity, and electability.